An Improved Features of Health Screening Test System for Malaysian Social Security Organisation (SOCSO) Programme - A. R. Abdullah; A. R. Syafeeza; M. A. U. C. Mood; T. N. S. T. Zawawi; A. R. Munzier (Institute of Advanced Engineering and Science, 2017)
The purpose of this paper is to improve the features of Health Screening Test System (HSTS) on Social Security Organization (SOCSO) program as physical evaluation for musculoskeletal disable workers (MSDs). SOCSO existing functional testing system are not suitable because of the evaluation was recorded manually peg board too high for Asian people. The occupational therapist whose involve in all the procedures is just doing the judgment in times to determine the capability of the patients. The functional capacity evaluation (FCE) technique is based on the functional range of motion evaluation that consist of positional tolerance respecting to time-motion testing on HSTS peg board and it is by referring to the original work movement. The main features of HSTS are able to measure speed, acceleration and evaluation of SOCSO’s patients for returning to work based on SOCSO’s requirement. In order to validate the accuracy of the proposed model, HSTS is used to evaluate the patient’s positional tolerance and then the result would be compare over the time frame which is Method Time Measurement (MTM) standard. This method is able to provide information and feedback for therapies as a status of patients. It is found that the proposed model is superior in getting the accurate time test for patient’s movements besides practicable and suitable for physical evaluation on MSD patients.